Analisis Peningkatan Penerimaan Pajak Air Permukaan dan Retribusi Daerah Pada Tahun 2018 – 2022 di Samsat Kabupaten Bekasi - Rahmawati, Almaida (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted with the aim of knowing and analyzing the increase in Surface Water Tax and Regional Retribution revenues in SAMSAT Bekasi Regency. The sample of this research is Surface Water Tax and Regional Retribution data for 2018 – 2022. Using a qualitative method with a descriptive approach. The results showed that the average level of effectiveness of Surface Water Tax and Regional Levies was 105.59% and 136.67% which could be categorized as very effective. The increase in the target value that was not achieved in 2021 resulted in a significant increase in revenue. Therefore, this increase in Surface Water Tax Revenue and Regional Levies affects an increase in Local Own Revenue with the realization of targets achieved and a high level of effectiveness.